The Pedagogical Role of Islamic Religious Teachers in Guiding Students’ Self-Control in Secondary Schools - Ahmad Luthfi (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the pedagogical role of Islamic religious teachers in guiding students’ self-control at Madrasah Aliyah Zakiyun Najah, located in Firdaus Village, Sei Rampah District, Serdang Bedagai Regency. The research employs a field study method with a descriptive-analytical narrative approach. Primary data were obtained through direct observation and in-depth interviews with Islamic religious teachers and seventh-grade students as key informants. Data analysis was conducted through stages of reduction, categorization, and narrative interpretation to reveal the pedagogical meaning of the implemented teaching practices. The findings indicate that Islamic religious teachers play a strategic role through three main approaches: habituation of moral values, demonstration of moral exemplarity in daily behavior, and the application of educational sanctions that emphasize character formation. These approaches contribute to the development of students’ religious character, internal discipline, and the ability to regulate emotions and actions in accordance with Islamic ethical norms.